Monitoring internal training load, stress-recovery responses, and immune-endocrine parameters in Brazilian Jiu-Jitsu training - Campos, F.; Molina Correa, J. C.; Canevari, V.; Branco, B. H.; Andreato, L. V.; de Paula Ramos, S. (The Journal of Strength and Conditioning Research, 2022)
This study aimed to evaluate the relationship between training loads, stress, and immune-endocrine markers during a precompetitive period in Brazilian jiu-jitsu (BJJ) athletes. For this, 12 athletes were submitted to 1 physical and 1 technical-tactical training session per day, 5 days a week, for 7 weeks. The saliva sampling and physical tests (countermovement jump [CMJ] and squat jump [SJ]) were performed before starting the training period (pre) and at the fourth week (4-week) and eighth week (post). Session rating of perceived exertion (sRPE) and the Recovery-Stress Questionnaire-Sport (RESTQ) were applied, and the training load was calculated weekly. Repeated-measures analysis of variance and the Friedman test were used, with significance levels set at p < 0.05. Increased training loads were recorded by the sRPE method in technical-tactical training sessions (p < 0.05). Higher physical loads were reported by athletes during weeks 1-4, contributing to overall higher training load, monotony, and strain during this period (p < 0.05). Increased perception of stress, by the RESTQ, and cortisol were detected, whereas decreased salivary testosterone and salivary immunoglobulin A were observed at 4 weeks (p < 0.05). No significant differences were detected in CMJ and SJ tests, suggesting that training neither elicited significant fatigue and underperformance nor improved strength performance. However, decreasing physical training loads appeared to reduce symptoms of stress and improved recovery, favoring immune recovery and anabolic balance. Thus, the sRPE seems to be a reliable and simple method to monitor training loads in BJJ athletes because variation in values was related to the RESTQ and physiological responses to training loads.